2015
DOI: 10.5268/iw-5.2.761
|View full text |Cite
|
Sign up to set email alerts
|

Mean diel variability of surface energy fluxes over Manso Reservoir

Abstract: Mean diel cycle of latent (E), sensible (H), net longwave (Lw net ), net shortwave (Sw), and net surface heat flux balance (S) were estimated from hourly meteorological and subsurface water temperature time series acquired for ~1 month during mid-austral autumn by a buoy system in a large tropical reservoir in Brazil. E and H were in phase and had their maximum (E = 163 Wm ). Mean Lw net varied from 76 at late afternoon to 89 Wm −2 at early morning, indicating its importance in the overall surface heat flux ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“…In addition, many earlier studies that have calculated surface heat fluxes from lakes have used remotely sensed water temperature in combination with land-based meteorological measurements (Derecki 1981;Croley 1989;Lofgren and Zhu 2000) or reanalysis data (Moukomla and Blanken 2017), which can lead to erroneous estimates of air-water interactions. Studies that have calculated heat fluxes using in situ temperature and meteorology data have dealt primarily with single lakes (Laird and Kristovich 2002;MacIntyre et al 2002;Lenters et al 2005;Verburg and Antenucci 2010;Lorenzzetti et al 2015;Dias and Vissotto 2017), or a number of lakes from a confined region (Woolway et al 2015b). Prior to this investigation, no known previous studies have compared turbulent surface fluxes from continuously recorded buoy data at so many lakes across the globe and at diel, seasonal, and annual timescales.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many earlier studies that have calculated surface heat fluxes from lakes have used remotely sensed water temperature in combination with land-based meteorological measurements (Derecki 1981;Croley 1989;Lofgren and Zhu 2000) or reanalysis data (Moukomla and Blanken 2017), which can lead to erroneous estimates of air-water interactions. Studies that have calculated heat fluxes using in situ temperature and meteorology data have dealt primarily with single lakes (Laird and Kristovich 2002;MacIntyre et al 2002;Lenters et al 2005;Verburg and Antenucci 2010;Lorenzzetti et al 2015;Dias and Vissotto 2017), or a number of lakes from a confined region (Woolway et al 2015b). Prior to this investigation, no known previous studies have compared turbulent surface fluxes from continuously recorded buoy data at so many lakes across the globe and at diel, seasonal, and annual timescales.…”
Section: Discussionmentioning
confidence: 99%
“…This global‐scale analysis has identified latitude and lake surface area as significant predictors of the variability in ABL stability over lake surfaces. Previous studies have shown evidence of a high incidence of unstable ABL conditions and its influence on the turbulent energy fluxes in individual lakes [ Verburg and Antenucci , ; Lorenzzetti et al ., ; Yusup and Liu , ]. This paper investigated the effects of geographic location and lake morphometry on ABL stability, the turbulent transfer coefficients, and on energy fluxes across the air‐water interface.…”
Section: Discussionmentioning
confidence: 99%
“…Doran et al [31] imposed a simple linear decrease of wind speed with distance to derive Equation (4). Figure 6a shows the typical diurnal cycle of the fluxes H observed during the dry season for the Brazilian Cerrado (wooded grassland, savanna) [43] and for a typical Brazilian tropical reservoir [44].…”
Section: Identification Of Lake Breeze From In Situ Datamentioning
confidence: 99%